2010
DOI: 10.1049/el.2010.0437
|View full text |Cite
|
Sign up to set email alerts
|

Analogue wavelet transform with single biquad stage per scale

Abstract: A new approach to obtain the wavelet transform with easily constructed analogue circuits is presented. It is shown that the impulse response of a bandpass biquad filter satisfies the conditions to be considered a mother wavelet. Using this, an integrated circuit performing the wavelet transform at 16 scales along eight octaves has been designed. The design has CMOS transistors working in the subthreshold region with a total power consumption of 650 nW. On-chip measurements are reported.Introduction: Traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…We will denote this frequency range as L. For this approximation, the condition for perfect reconstruction is M m=0 χH(r m ω) = 1, for ω ∈ L. To validate the proposed approach, the simple approximation has been on-chip fabricated for H(ω), r, M , and χ given in Table I. In [2] it is shown that the IR of this H(ω) satisfies the mathematical conditions to be used as a mother wavelet. The χ value is selected to normalize the system gain.…”
Section: Approximations Of the Semidiscrete Inverse Wavelet Transformmentioning
confidence: 99%
See 3 more Smart Citations
“…We will denote this frequency range as L. For this approximation, the condition for perfect reconstruction is M m=0 χH(r m ω) = 1, for ω ∈ L. To validate the proposed approach, the simple approximation has been on-chip fabricated for H(ω), r, M , and χ given in Table I. In [2] it is shown that the IR of this H(ω) satisfies the mathematical conditions to be used as a mother wavelet. The χ value is selected to normalize the system gain.…”
Section: Approximations Of the Semidiscrete Inverse Wavelet Transformmentioning
confidence: 99%
“…3b. This OTA has a differential input range of ±29 mV within 1% of linearity [2]. The OTA transistors have the following dimensions in μm/μm: 36/4.5 for M 1 to M 4 , 17/4.5 for M 5 and M 6 , and 10/4.5 for M 7 and M 8 .…”
Section: Circuit Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to overcome these difficulties, a number of attempts at analog hardware implementations of the continuous wavelet transform have been reported recently. Previous studies on analog hardware implementation of WT can be divided into two categories, namely time-domain approach [2][3][4] and frequency-domain approach [5]- [11]. The latter is now the mainstream approach and the performance of such implementation primarily depends on the accuracy of the corresponding wavelet approximations.…”
Section: Introductionmentioning
confidence: 99%